Pharmaceutical amorphous solid dispersions - Newman, Ann (Pharmaceutical scientist) (Wiley, 2015)
Providing a roadmap from early to late stages of drug development, this book overviews amorphous solid dispersion technology - a leading platform to deliver poorly water soluble drugs, a major hurdle in today's pharmaceutical industry. Helps readers understand amorphous solid dispersions and apply techniques to particular pharmaceutical systems Covers physical and chemical properties, screening, scale-up, formulation, drug product manufacture, intellectual property, and regulatory considerations Has an appendix with structure and property information for polymers commonly used in drug development and with marketed drugs developed using the amorphous sold dispersion approach Addresses global regulatory issues including USA regulations, ICH guidelines, and patent concerns around the world.